Comparison of surgical trends in zone 2 flexor tendon repair between Turkish and international surgeons - Seyyid Serif Unsal; Tugrul Yildirim; Mehmet Armangil (Acta Orthopaedica et Traumatologica Turcica, 2019)
Objectives: The aim of this study was to evaluate Turkish trends in zone 2 flexor repair with regards to surgical technique, suture materials, anesthesia and post-operative rehabilitation and compare this with international surgeons by modifying Gibson's survey. Methods: A printed and online survey consisting of 19 questions modified from Gibson's survey was sent to 590 Turkish and international surgeons. The surgeon's years in practice, province of practice, residency type, number of zone 2 flexor tendon repairs done in a year, preferred surgical technique, suture material, complications and postoperative protocols were asked to the respondents. Results: A total of 194 surgeons completed the survey (a 25% response rate). Of those who completed the survey, 91 were international (mostly from far eastern countries) and 103 were Turkish surgeons. Years in practice and educational background had influence on the decision-making. There were differences between the Turkish and international surgeons in the core and epitendinous suture thickness preference and flexor tendon sheath repair. There was a statistically significant relationship between the province of practice and the use of WALANT (Wide awake local anesthesia no tourniquet) (p < 0.05). While the majority of respondents who preferred postoperative early passive motion protocol were from Turkey (61.5%), the majority of respondents who preferred early active motion protocol were practicing abroad (73.9%). Conclusion: Despite some variations the surgeons involved in this study follow to a large extent the current literature. Keywords: Flexor tendon, Zone II repair, Suture materials, Surgical trends, Survey